Empowering The Social Capital in The Religion-Based Character Education for The Elementary School Children in The Al-Irsyad 02 Elementary School Purwokerto - Ningsih, Tutuk (International Conference of Moslem Society, 2016)
The study discussed the use of social capital in the religion-based character education for the elementary school children in the Al-Irsyad 02 Elementary School Purwokerto. The objectives of the study were to: (1) study the use of social capital in the religion-based character education within the learning process by means intracurricular and extracurricular activities and of school culture; (2) view the religion-based character education based on the aspect of cohesiveness and cooperation; and (3) view the religion-based character education based on the aspect of tolerance-solidarity within the learning process. For the data collection, the researcher performed the observation, the interview and the documentation. Then, in conducting the study the researcher selected the descriptive technique as the data analysis technique because the researcher would like to describe the data in order to solve the problem. Based on the results of the study, the researcher would like to draw the following conclusions. First, the social capital in the religion-based character education by means of teaching-learning process (intracurricular activities) has positive and important role for developing the character values of the students in the Al-Irsyad 02 Elementary School Purwokerto. The social capital in the religion-based character education becomes one of the school agendas in building the studentsâ€™ potentials and competencies. The extracurricular activities also have positive role in supporting the process of internalizing the character values into the school community since the extracurricular activities, along with the intracurricular activities, have been related to the social and the religious aspects. Next, the culture of Al-Irsyad 02 Elementary School Purwokerto might be summarized into eight aspects. Second, the use of social capital, according to the perspective of cohesiveness and cooperation, within the daily learning process has been based on the religious values. The students of the elementary school always pray, do the dzikir and read the Koran every morning. The cohesiveness has enhanced the studentsâ€™ discipline and solidarity and has created the studentsâ€™ religious characteristics. Third, the use of social capital, according to the perspective of the aspects of solidarity and tolerance, within the religion-based character education has taken the form of social activities. For example, Al-Irsyad 02 Elementary School Purwokerto always holds the Open House event every second semester for each year and the objective of the event is to perform the syiar and the promotion. The event has been introduced by the elementary school since Al-Irsyad 02 Elementary School Purwokerto has the following slogan: â€œThe Champion School.â€ The meaning of the slogan is that the elementary school becomes the place that gives birth to the national and the international champions. The elementary school, in other words, has been teaching their students to have good social characteristics.